Targeting Myeloid-Derived Suppressor Cells to Enhance a Trans-Sialidase-Based Vaccine Against Trypanosoma cruzi - Gamba, Juan Cruz; Roldán, Carolina; Prochetto, Estefanía; Lupi, Giuliana; Bontempi, Iván; Poncini, Carolina Verónica; Vermeulen, Mónica; Pérez, Ana Rosa; Marcipar, Iván; Cabrera, Gabriel (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma cruzi (T. cruzi) is a protozoan parasite that causes Chagas disease, a neglected tropical disease that affects more than 6 million people around the world, mostly in Latin America. The fact that there is no vaccine available after intense research suggests that new approaches are needed to further improve vaccine efficacy. It is well established that experimental T. cruzi infection induces a marked immunosuppressed state, which includes notably increases of CD11b+ GR-1+ myeloid-derived suppressor cells (MDSCs) in the spleen, liver and heart of infected mice. We have previously shown that a trans-sialidase based vaccine (TSf-ISPA) confers protection against a virulent T. cruzi strain, stimulating the effector immune response and decreasing significantly CD11b+ GR-1+ splenocytes. Here, we show that even in the immunological context elicited by the TSf-ISPA vaccine, the remaining MDSCs are still able to influence several immune populations. Depletion of MDSCs with 5 fluorouracil (5FU) at day 15 post-infection notably reshaped the immune response. After 21 days post- infection, TSf-ISPA vaccinated and 5FU treated mice showed a marked increase of the CD8 response, an increase in the percentage and number of CD4+ Foxp3+ Tregs cells and changes in the phenotype, percentage and number of CD11chigh dendritic cells. Of note, although MDSCs depletion at day 15 post-infection did not ameliorated survival or parasitemia levels, depletion of MDSCs during the first week of infection caused a beneficial trend regarding parasitemia and mice survival of vaccinated mice, supporting the possibility to target MDSCs from different approaches to enhance vaccine efficacy. Finally, since we have previously shown that TSf-ISPA immunization causes a slight but significant increase of CD11b+ GR-1+ splenocytes, here we also targeted those cells at the stage of immunization. Notably, 5FU administration before each dose of TSf-ISPA vaccine was able to significantly ameliorate survival and decrease parasitemia levels of vaccinated and infected mice. Taken together, this work supports that MDSCs strongly modulate the immune response even in vaccinated mice and that targeting those cells may represent a valuable tool during vaccine design against T. cruzi, and likely for other pathologies that are characterized by the subversion of the immune system.